A compensation of VANETs with UAVs to optimizing the routing strategy - Ali, Rabei Raad; Alzakwani, Mujahid Hamood Hilal; Waisi, Najwan Zuhair; Jubair, Mohammed Ahmed; Najjaw, Mahmood Sh (Edelweiss Applied Science and Technology, 2025)
VANETs (Vehicular Ad Hoc Networks) played a vital role in the infrastructure of smart cities due to intelligent communication systems. VANETs exhibit unique characteristics, such as high speeds and unpredictable mobility, which lead to challenges such as overhead, delay, and link failure. Therefore, Unmanned Aerial Vehicles (UAVs) are introduced to mitigate ground-level issues, with communication managed through the air medium used to address these problems. Routing also needs to be enhanced for effective communication in UAV-assisted VANETs. This paper proposes an Advanced UAV Communication Strategy for VANETs (AUCS-VANETs) approach to optimize the routing protocol. The strategy selects the shortest route from source to calculate the vehicle’s potential future delay and employs the Probability Distribution Function (PDF) through Bayes’ model. We use NS2 and SUMO in the simulation as well as four parameters for testing (“Packet Delivery Ratio” (PDR), “End-To-End” (E2E) delay, “Routing Overhead” (RO), and “Throughput” (TP). The experiment results show that the AUCS-VANETs approach achieves higher PDR and TP, along with lower E2E delay and RO compared to earlier approaches.